A low-cost innovation design for portable rubbish cage trap (PRCT) in drain system - Ahmad, Noor Aliza; Zainal, Intan; Md Ali, Zarina (2023)
One of the primary contributors to water pollution is the presence of solid waste or rubbish within the drainage system. Moreover, the presence of an obstruction within the drainage system would impede the movement of water, so leading to the occurrence of a flood. Based on the given circumstances, a recommended solution to address the issue involves the utilisation of a Portable Rubbish Cage Trap (PRCT). This research seeks to investigate and assess hydraulic features such flow rate, total amount of collected garbage, and rainfall distribution, in addition to proposing an innovative design of a PRCT employing reusable and recycled materials from a building site. The components of PRCT are cable ties, grey polyvinyl chloride (PVC) tubing, and green netting available in two sizes. To produce a low-cost project, these materials are collected from rubbish found on building sites. The drainage line under investigation is situated in Taman Universiti, Johor Bahru. The study aims to compare the data obtained from previous data using Mesh type cage and analysis performed in this study includes the measurement of the weight of the collected waste in the PRCT, the examination of rainfall patterns, and the assessment of the hydraulic properties affecting the effluent flow rate over a two-week period. The investigation reveals that the Mesh Type wall has a higher weight of imprisoned waste 388.52 kg compared to the PRCT with 339.3 kg. The mean flow rates for the Mesh type cage and PRCT are 7.43 mm3 /s and 39.2 mm3 /s, respectively. The highest recorded rainfall distribution in October 2020 was 39 mm, while the highest recorded weight was 57.3 kg. The market potential of the PRCT can be enhanced by ensuring cost-effective measures for collecting construction waste materials and labour, as well as by improving the durability of the PRCT